Intensification of a solar photo-Fenton reaction at near neutral pH with ferrioxalate complexes: A case study on diclofenac removal from aqueous solutions - Bianca M. Souza (2014)
The kinetic degradation profile for diclofenac (DCF) antibiotic in aqueous solutions using the conventional photo-Fenton reaction is characterized by a very slow reaction rate mainly associated to DCF precipitation-redissolution-degradation mechanism at acidic conditions and DCF degradation via a ligand-to-metal charge mechanism that occurs on the surface of the iron precipitates, under neutral pH conditions. This work evaluates the intensification of a solar photo-Fenton reaction by using ferrioxalate complexes (Fe3+/H2O2/oxalic acid/UVA-vis) in the degradation of diclofenac (DCF) in aqueous solution at near neutral pH values, which avoids the precipitation of DCF and ferric hydroxide, and iron concentrations below the discharge limits into water bodies ([Fe] <= 2.0 mg/L). The efficiency of the photo-Fenton process was evaluated at different iron/oxalate molar ratios (1:3; 1:6 and 1:9; [Fe3+] = 2 mg/L), under controlled conditions of pH (5.0 and 6.0), using a lab-scale photoreactor irradiated with artificial sunlight. At pH 6.0 ([DCF]0 = 20 mg/L), using an iron/oxalate molar ratio of 1:9 it was achieved complete degradation of DCF (below the detection limit) and 63.0% mineralization in 90 min, consuming 1.9 mM H2O2. A lower dose of oxalic acid (1:3 iron/oxalate molar ratio) was needed to attain similar results at pH 5.0. DCF degradation at pH 5.0, for an iron/oxalate molar ratio of 1:3, was also evaluated at different temperatures (15-45 degrees C), UVA irradiances (27.8-59.9 W-UV/m(2)), DCF and iron concentrations ([DCF] = 2-20 mg/L, [Fe3+] = 1-2 mg/L), presence of inorganic ions (0.1 g/L; Cl-, SO42-, NO3-, HCO3-, NH4+) and radical scavengers (sodium azide 10 mM and D-mannitol 50 mM). DCF degradation kinetics at pilot plant scale under natural solar radiation, using the best conditions obtained at lab-scale (pH 5.0, iron/oxalate molar ratio of 1:3), showed similar results to those obtained in the lab-scale photoreactor. The